Long-term Cross-reactivity Against Nonvaccine Human Papillomavirus Types 31 and 45 After 2- or 3-Dose Schedules of the AS04-Adjuvanted Human HPV-16/18 Vaccine - Folschweiller, Nicolas (J Infect Dis, 2019)
This analysis focused on long-term cross-reactive immunogenicity against nonvaccine human papillomavirus (HPV) types 31 and 45 following 2 doses of AS04-adjuvanted HPV-16/18 vaccine in girls aged 9–14 years or following 3 doses in women aged 15–25 years, for up to 3 years (HPV-070 study) and up to 5 years (HPV-048 study) after the first vaccination. Both schedules elicited antibodies against HPV-31 and HPV-45 up to 5 years after first dose. The antibody concentration was similar in young girls as compared to women. Specific CD4(+) T-cell and B-cell responses to HPV-31 and HPV-45 at month 36 were similar across groups. Clinical trials registration: NCT01381575 and NCT00541970.